Issues of developing the speed ability of students playing Basketball - Gantulga, Ragchaa; Ri Mu Tu, Bai Ji; Sumiyabeis, Tserennadmid; Erdenepurev, Lkhagva (Proceedings of the Mongolian Academy of Sciences, 2024)
The purpose of this study is to improve the content and methodologies of the curriculum of the training courses for the development of the speed ability of high school students, who practice basketball. When developing the speed capacity of the high school students of National Secondary School of Horinger country of Hohhot, Inner Mongolia, People's Republic of China, a Chinese researcher Li Wenlong (2015) used the theory and concept that "an important part of training of basketball players is to develop their speed capacity by improving their strength capacity." Movement test methodology was used to determine the general speed ability of the students and the basic technical speed level of basketball and consequently, to calculate the results [3]. A program developed to study respondents' general speed and basketball speed revealed that a 30-meter run was improved by 0.51 sec, 50-meter run by 0.72 sec, and 100-meter run by 0.36 sec. According to the basic technical parameters of basketball, the speed during straight dribbling increased by 0.56 seconds, the dibbling speed around the 15 mark increased by 0.38 seconds, the speed of two students running and passing ball on a 28-meter court increased by 0.78 seconds, and the speed of the defensive transition improved by 4 times. We believe that the capacity of targeted exercises, tools, and exercise selection in the curriculum and planning models used in our study have become efficient.